The Influence of Education and Training (Diklat), Competency on Position Promotion and Employee Performance of Eco Beach Villa and Apartment Canggu - Wibisono, Gunawan; Nugraha, Surya (Jurnal Manajemen Pelayanan Hotel, 2023)
This research aims to analyze the influence of education and training (Diklat), competency on position promotion and employee performance at Eco Beach Villa and Canggu Apartments in companies in the tourism industry sector in Badung district. In this study, the population studied was 216 permanent employees at Eco Beach Villa and Apartment Canggu. This research sample used the Solvin formula to obtain 68 people. The analysis technique used is "path analysis". The analysis results show that: 1). Education and training have a positive and significant effect on the work performance of Eco Beach Villa and Apartment Canggu employees; 2). Competence has a positive and significant effect on the performance of Eco Beach Villa and Apartment Canggu employees; 3). Education and training have a direct influence on the promotion of Eco Beach Villa and Apartment Canggu employees; 4). Competency has a direct influence on the promotion of Eco Beach Villa and Apartment Canggu employees; 5). Job promotions have a direct effect on the performance of Eco Beach Villa and Apartment Canggu employees; 6). Education and training have a significant indirect effect on the performance of Eco Beach Villa and Apartment Canggu employees through job promotions; 7). Competency has a significant indirect effect on the performance of Eco Beach Villa and Apartment Canggu employees through job promotions. Keywords: Education and Training, Competency, Position Promotion, Employee Performance.